A Novel Thoracic Ultrasound Measurement After Congenital Diaphragmatic Hernia Repair Identifies Decreased Diaphragmatic Excursion Associated With Adverse Respiratory and Surgical Outcomes - Ross, James T.; Liang, Norah E.; Phelps, Andrew S.; Squillaro, Anthony I.; Vu, Lan T. (Frontiers in Pediatrics, 2021)
Background and Aim: Congenital diaphragmatic hernia (CDH) is a rare defect often associated with pulmonary hypoplasia and abnormal pulmonary vascular development. Even after successful hernia repair, pulmonary disease may persist into adulthood. Impaired diaphragmatic motility may lead to compromised respiratory function long after index repair. This study investigates whether a novel ultrasound measurement, the diaphragmatic excursion ratio, can be a simple and non-invasive method to evaluate routine diaphragmatic motion after CDH repair, and whether it correlates with adverse surgical and respiratory outcomes. Materials and methods: A cross-sectional study was conducted in consecutive patients who presented at medium-term follow-up visit between December 2017 and December 2018 after CDH repair at single pediatric hospital. Transthoracic ultrasound was performed with craniocaudal diaphragmatic excursion measured bilaterally during routine breathing. Diaphragmatic excursion ratios (diaphragmatic excursion of repaired vs. unrepaired side) were calculated and retrospectively compared with clinical data including demographics, length of stay, respiratory adjuncts, oral feeding, and need for gastrostomy. Results: Thirty-eight patients (median age at ultrasound, 24 months, interquartile range 11-60) were evaluated. Nine patients underwent primary repair, 29 had non-primary repair (internal oblique muscle flap or mesh patch). Patients with a diaphragmatic excursion ratio below the median (0.54) had longer hospital stays (median 77 versus 28 days, p = 0.0007) more ventilator days (median 16 vs. 9 days, p =0.004), and were more likely to have been discharged on oxygen (68% versus 16%, p = 0.001). They were also less likely to be exclusively taking oral feeds at 1-year post-surgery (37% versus 74%, p = 0.02) and more likely to require a gastrostomy tube in the first year of life (74% versus 21%, p = 0.003). Conclusions: Transthoracic ultrasound after CDH repair is practical method to assess diaphragm motion, and decreased diaphragm excursion ratio is associated with worse respiratory outcomes, a longer length of stay, and dependence on gastrostomy tube feeding within 1 year. Further prospective studies may help validate this novel ultrasound measurement and offer prognostic value.